Impact of power interruptions on national economy. - Viray, Francisco L.
This paper shows that there is a significant correlation between energy consumption and national income or output. Thus, it is inferred that power interruptions and shortages result to losses in national income. The study specifically deals with the impact of such power interruptions and shortages on the manufacturing industries, the sector in the economy that uses electric energy most intensively and which has one of the largest contributions to national income. To quantify the impact of power interruptions on national economy, a simplistic approach is presented. Estimating graphs are generated for each industry group of the manufacturing sector as well as for the whole manufacturing industry.